Multiparty system as a basis for forming of sovereign political system of Kazakhstan - Kozhakhmetov, G.Z.; Badanova, M.M. (KSU Publ., 2014)
This article discusses the political system of the Republic of Kazakhstan, including the formation of a multiparty system. Position of the parties in the state is determined by several regulations. Scientific study of the legal status of political parties is important for the resolution of practical and legal problems of the development of this phenomenon in our society. Background research is that theoretical and practical problems of legal regulation and development of political parties among the priorities and are traditionally the focus of both foreign and domestic legal and political science.
Көп партиялық егеменді Қазақстанның саяси жүйесінің қалыптасуының негізі ретінде
Многопартийность как основа формирования политической системы суверенного Казахстана
Keywords: Republic of Kazakhstan; Commonwealth of Independent States; pathogenesis; multiparty system; political parties